Pengembangan Tes Kemampuan Bahasa Inggris Untuk Keterampilan Berbahasa Reseptif Bagi Mahasiswa Fakultas Ilmu Keolahragaan - Rizka Safriyani, (Kepelatihan Olahraga, 2011)
Listening and reading are receptive skills because learners do not produce language to do these. In the process of learning a new language, learners begin with receptive skills and then later move on production use. Both receptive and productive skills are important to achieve communicative competence. Developing listening and reading test are related to the materials, the test level, and type of test item formats. It will give various type of learning activities and improve students competence in English as well.